Isolation, structure elucidation and cytotoxic activity of cucurbitacins from Elaeocarpus petiolatus - Cho, Eun Seon (2019)
Four new cucurbitacins (1-4) along with six known compounds, namely, 16α,23α-epoxy-3β,20β-dihydroxy-10αH,23βH-cucurbit-5,24-dien-11-one (5), 16α,23α-epoxy-3β,20β-dihydroxy-10αH,23βH-cucurbit-5,24-dien-11-one 3-O-β-D-glucopyranoside (6), elaeocarpucin F (7), hexanocucurbitacin F (8), β-sitosterol (9), and vomifoliol (10), were isolated from the leaves and bark of Elaeocarpus petiolatus. The structures of the new cucurbitacin compounds were elucidated based on detailed analyses of their 1D and 2D NMR, HRESIMS and MS data. The absolute configuration of compound 1 was established by X-ray diffraction analysis. Compound 1 represents a rare cucurbitacin incorporating an unusual furan-bearing side chain with ketal and epoxide functions, while compound 2 possesses a rare six-fused ring system incorporating a pyranofuranyl ring system. Compound 3 is a new C-5,C-6-epoxide containing cucurbitacin, while compound 4 represents a new acetate derivative of the known cucurbitacin glycoside 6. Compounds 1, 2 and 4 were assessed for their anticancer activity in vitro by using a panel of human cancer cell types, including breast, pancreatic, nasopharyngeal and colon cancer cells. The pure compound 1 showed good cytotoxic effects on breast cancer cell lines (MDA-MB-468, MDA-MB-231, MCF7 and SKBR3) and colorectal cancer cell line (SW48). On the other hand, compound 2 only showed appreciable potency against the MDA-MB-468 and MDA-MB-231 breast cancer cell lines, while compound 4 only showed appreciable potency against the MDA-MB-468 cell line. Further mechanistic investigations are still necessitated in order to determine the potential therapeutic application of these three pure compounds.